International child law - Buck, Trevor, 1951-; Buck, Trevor, 1951- (Abingdon, Oxon : Routledge, 2011)
Rev. ed. of : International child law / Trevor Buck.
Includes bibliographical references and index.
Keywords: Children (International law); Children -- Legal status, laws, etc